Erythema nodosum as a manifestation of HIV infection - Louthrenoo W. (2014)
Various musculoskeletal syndromes have been well described in patients infected with the human immunodeficiency virus (HIV). Surprisingly, erythema nodosum, an inflammation of the adipose tissue of the skin, has rarely been described. We report a 24-year-old known case of HIV infection, who developed fever and multiple tender subcutaneous nodules that were proven to be erythema nodosum. The patient also had polymyositis. She responded well to a high dose of corticosteroids. Erythema nodosum should be listed as possible the rheumatic manifestation of HIV infection.